Aplicación del razonamiento lógico matemático en el rincón de construcción - Fernández Fernández, Hipatia Carolina (2016)
This research has as aim to raise activities of logical mathematical reasoning thus giving the proper use the corner of construction because it is a fun and confortable place for activities related to mathematics, for the research was used the mixed investigation with its description and real data which ones allowed to detect the absence of activities which stimulate the cognitive development of the children in the corner of the construction, it is for this reason that innovative activities were collected that serve as a didactic guide where their contents will be exclusively activities of logical mathematical reasoning the same which will contribute directly to benefit children of early education of the Educative Unit "Ramon Barba Naranjo" as well as indirectly to teachers, parents and authorities of the institution. The methodology used is inductive because it requires the observation technique that will let to visualize the benefits that mathematics will provide in the cognitive process of the children and the observation sheet will used as an assessment tool. Also it is based on the contributions of Jean Piaget who said that children are able to solve various problems with the cognitive part and Maria Montessori who that said that works with preschool children it is essential in a suitable environment with materials according to the age of the children; and that teachers are only guides in order to help to the student to build their own learning which will allow them to get fundaments for their personal and integral development in society. The techniques used in the proposal are: the survey for early education teachers and an observation sheet for children. In the investigation it was verified that the logical mathematical reasoning is essential and it is present in the daily lives of humans.